1992
DOI: 10.1021/bi00120a014
|View full text |Cite
|
Sign up to set email alerts
|

Noncovalent interactions of poly(adenosine diphosphate ribose) with histones

Abstract: Covalent linkage of ADP-ribose polymers to proteins is generally considered essential for the posttranslational modification of protein function by poly(ADP-ribosyl)ation. Here we demonstrate an alternative way by which ADP-ribose polymers may modify protein function. Using a highly stringent binding assay in combination with DNA sequencing gels, we found that ADP-ribose polymers bind noncovalently to a specific group of chromatin proteins, i.e., histones H1, H2A, H2B, H3, and H4 and protamine. This binding re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
104
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 118 publications
(116 citation statements)
references
References 24 publications
12
104
0
Order By: Relevance
“…To visualize the possible affinity of NMNAT-1 for PARP-1, purified NMNAT-1 that had been immobilized on nitrocellulose was incubated with purified 32 P-labeled poly(ADPribosyl)ated PARP-1, protein-free 32 P-labeled PAR, or 32 Plabeled oligo(ADP-ribosyl)ated PARP-1 (42). The latter was obtained by automodification of PARP-1 in the presence of Ϸ10 nM 32 P-labeled NAD ϩ , thereby attaching only short radiolabeled ADP-ribose oligomers and enabling the detection of PARP-1 binding (43).…”
Section: Resultsmentioning
confidence: 99%
“…To visualize the possible affinity of NMNAT-1 for PARP-1, purified NMNAT-1 that had been immobilized on nitrocellulose was incubated with purified 32 P-labeled poly(ADPribosyl)ated PARP-1, protein-free 32 P-labeled PAR, or 32 Plabeled oligo(ADP-ribosyl)ated PARP-1 (42). The latter was obtained by automodification of PARP-1 in the presence of Ϸ10 nM 32 P-labeled NAD ϩ , thereby attaching only short radiolabeled ADP-ribose oligomers and enabling the detection of PARP-1 binding (43).…”
Section: Resultsmentioning
confidence: 99%
“…Considering the chemical structure of polymers, they resemble nucleic acids with a great number of negative charges that modify the acceptor proteins. This very strong interaction (Panzeter et al, 1992) introduces, therefore, a structural and functional modification of these proteins, supporting a role for ADP-ribose polymers as 'molecular adaptors'. The interaction between the polymers and the modified proteins is nonionic in nature since it does not depend on the basic charge of proteins; rather, it depends on the presence of a particular amino-acid motif, which represents the consensus domain for the noncovalent link with ADPribose polymers (Schmitz et al, 1998;Pleschke et al, 2000).…”
Section: Introductionmentioning
confidence: 92%
“…Each residue in PAR contains an adenine moiety capable of base stacking and hydrogen bonding, as well as two phosphate groups that carry negative charges (Amé et al 2000). PAR may form definitive structures through intramolecular interactions (Minaga and Kun 1983a,b), and these structures have the potential for noncovalent attractive (or repulsive) interactions with other molecules (Mathis and Althaus 1987;Wesierska-Gadek and Sauermann 1988;Panzeter et al 1992). Thus, PAR may alter protein activity by functioning as a site-specific covalent modification, a protein-binding matrix, or a steric block.…”
Section: The Chemical Biology Of Parmentioning
confidence: 99%
“…Note, however, that although much emphasis has been placed on histone proteins as targets for PARylation, PARP-1 itself is the primary target for PARylation in vivo, with >90% of PAR found on PARP-1 (Ogata et al 1981;Huletsky et al 1989;D'Amours et al 1999). Additional biochemical studies suggested that polyanionic PAR, either free or attached to proteins such as PARP-1, may provide an attractive matrix for histones released from destabilized nucleosomes (Mathis and Althaus 1987;Realini and Althaus 1992) or even strip basic proteins, such as histones, from DNA (Mathis and Althaus 1987;Wesierska-Gadek and Sauermann 1988;Panzeter et al 1992).…”
Section: Modification Of Chromatin Structurementioning
confidence: 99%